Effects of cytoplasm and reactant polarities on acid-catalyzed lipid transesterification in wet microalgal cells subjected to microwave irradiation. (January 2016) - Huang, Rui; Cheng, Jun; Qiu, Yi; Li, Tao; Zhou, Junhu; Cen, Kefa
Highlights: Cytoplasm and microwave change polarity of reactant and affect transesterification. Cytoplasm organic decrease contact angle of reactants by 13.92° and promote reaction. Hydrophilic algae biomass make apolar lipid more accessible to hydrophilic alcohol. Cytoplasm water increase contact angle of reactants and inhibit transesterification. Microwave decrease dielectric constant of alcohol and promote transesterification. Abstract: The polarities of the cytoplasm and reactants were measured through dielectric spectroscopy, contact angle test, NMR, and FTIR to investigate the mechanisms underlying acid-catalyzed lipid transesterification in wet microalgal cells subjected to microwave irradiation. Organics with apolar functional groups in the cytoplasm decreased the contact angle of methanol against triglyceride by 13.92°, which subsequently increased transesterification efficiency by 2.4 times. The microalgal biomass, given its higher hydrophilicity index of 1.96 than lipids, was more accessible to hydrophilic alcohols, which subsequently promoted transesterification. Water in the cytoplasm promoted the dielectric constant of methanol and increased the contact angle of methanol against triglyceride by 20.51°, which subsequently decreased transesterification efficiency by 72.6%. The inhibitory effect of water on transesterification weakened with the prolonged carbon lengths of the alcohols because of decreased polarity. Microwave decreased the electric constants of alcohols and reduced the polarity difference between alcohols and lipids, thereby improving transesterification efficiency.